Diversity and role of plasmids in adaptation of bacteria inhabiting the Lubin copper mine in Poland, an environment rich in heavy metals - Dziewit, Lukasz; Pyzik, Adam; Szuplewska, Magdalena; Matlakowska, Renata; Mielnicki, Sebastian; Wibberg, Daniel; Schlüter, Andreas; Pühler, Alfred; Bartosik, Dariusz (Frontiers in Microbiology, 2015)
The Lubin underground mine, is one of three mining divisions in the Lubin-Glogow Copper District in Lower Silesia province (Poland). It is the source of polymetallic ore that is rich in copper, silver and several heavy metals. Black shale is also significantly enriched in fossil organic matter in the form of long-chain hydrocarbons, polycyclic aromatic hydrocarbons, organic acids, esters, thiophenes and metalloporphyrins. Biological analyses have revealed that this environment is inhabited by extremophilic bacteria and fungi. Kupfershiefer black shale and samples of water, bottom and mineral sediments from the underground (below 600 m) Lubin mine were taken and twenty bacterial strains were isolated and characterized. All exhibited multi-resistant and hypertolerant phenotypes to heavy metals. We analyzed the plasmidome of these strains in order to evaluate the diversity and role of mobile DNA in adaptation to the harsh conditions of the mine environment. Experimental and bioinformatic analyses of 11 extrachromosomal replicons were performed. Three plasmids, including a broad-host-range replicon containing a Tn3 family transposon, carried genes conferring resistance to arsenic, cadmium, cobalt, mercury and zinc. Functional analysis revealed that the resistance modules exhibit host specificity, i.e. they may increase or decrease tolerance to toxic ions depending on the host strain. The other identified replicons showed diverse features. Among them we identified a catabolic plasmid encoding enzymes involved in the utilization of histidine and vanillate, a putative plasmid-like prophage carrying genes responsible for NAD biosynthesis, and two repABC-type plasmids containing virulence-associated genes. These findings provide an unique molecular insight into the pool of extrachromosomal replicons and highlight their role in the biology and adaptation of extremophilic bacteria inhabiting terrestrial deep subsurface.